Draft Annual Plan 1993-94 Mizoram - Planning Commission (Planning Commission, 1993)
About 70% of the approved Annual Plan outlay of Rs. 185.00 Crores will be utilised for important schemes and projects located in rural areas. Against the current year Annual Plan approved outlay of Rs. 166.00 Crores, the anticipated expenditure has been worked out at Rs. 167.67 Crores including Rs. 1.67 Crores of loan taken by P.H.E. Department.
Mizoram
Mizoram